The effectiveness of physio-chemical treatment of leachate from semi aerobic sanitary landfill, Pulau Burung, Pulau Pinang / Noraishah Mohamad Shani - Mohamad Shani, Noraishah (2006)
This study focused on leachate from Pulau Burung Sanitary Landfill. The Pulau Burung Sanitary landfill is semi-aerobic sanitary landfill and it uses physio-chemical treatment method. The objective of this research is to determine the turbidity, COD, pH, and temperature parameters in order to see the effectiveness of the treatment from point to point. Thus, the leachate was collected at every point of treatment in order to determine the parameters and to determine the effectiveness of the method applied. The effectiveness of the method used evaluated by looking at the controlled pH and temperature and removal of the leachate parameters such as COD and turbidity. The leachate collected for 8 weeks but only 6 weeks the data are successfully determined by using Hydro lab equipment and from the environment laboratory. The data analyzed and graphs were plot. From the graph, comparison on leachate quality before treatment, during treatment, and after treatment made to evaluate the effectiveness of the leachate treatment used. The results indicated that by using physio-chemical and semi-aerobic landfill treatment, it had effectively remove turbidity from around 129.8 NTU to 11.1 NTU, which comply with the standard of effluent discharge set by Environmental Quality Act 1974. However, the treatment is not effective for COD removal, which is from around 3690 mg/1 to 430 mg/1.